The Effectiveness of Problem-Based Learning Based on Dienes’ Theory with the Colored Biscuit Games on the Mathematical Problem-Solving Ability of Elemetary School Students - Salsabila Firda Azzahra; Imas Safitriani; Dina Pratiwi Dwi Santi; Irmawati Liliana Kusuma Dewi (Universitas Pendidikan Ganesha, 2025)
The lack of student interest in mathematics results in limited mathematical problem-solving skills. This study examines the effectiveness of the. Problem-Based Learning (PBL) model based on Dienes’ theory using coloured biscuit games on the mathematical problem-solving abilities of fifth-grade students in class V-A of an elementary school. The research employs a quantitative approach with a quasi-experimental method and a one-group pretest- posttest design. Data were collected through pretests and posttests and analyzed using validity and reliability tests, normality tests, paired sample t-tests, and N-Gain tests. The results show that the instruments are valid and reliable, the data are normally distributed, and there is a significant difference between pretest and posttest scores (p < 0.05). The average N-Gain score categorized as moderately effective. Thus, the Problem-Based Learning model based on Dienes’ theory using coloured biscuit games is proven to be moderately effective in improving elementary school student’s mathematical problem-solving abilities.